Impact of the Microscale Distribution of a Pseudomonas Strain Introduced into Soil on Potential Contacts with Indigenous Bacteria - Dechesne, Arnaud (American Society for Microbiology, 2005)
Soil bioaugmentation is a promising approach in soil bioremediation and agriculture. Nevertheless, our knowledge of the fate and activity of introduced bacteria in soil and thus of their impact on the soil environment is still limited. The microscale spatial distribution of introduced bacteria has rarely been studied, although it determines the encounter probability between introduced cells and any components of the soil ecosystem and thus plays a role in the ecology of introduced bacteria. For example, conjugal gene transfer from introduced bacteria to indigenous bacteria requires cell-to-cell contact, the probability of which depends on their spatial distribution. To quantitatively characterize the microscale distribution of an introduced bacterial population and its dynamics, a gfp-tagged derivative of Pseudomonas putida KT2440 was introduced by percolation in repacked soil columns. Initially, the introduced population was less widely spread at the microscale level than two model indigenous functional communities: the 2,4-dichlorophenoxyacetic acid degraders and the nitrifiers (each at 10(6) CFU g(−1) soil). When the soil was percolated with a substrate metabolizable by P. putida or incubated for 1 month, the microscale distribution of introduced bacteria was modified towards a more widely dispersed distribution. The quantitative data indicate that the microscale spatial distribution of an introduced strain may strongly limit its contacts with the members of an indigenous bacterial community. This could constitute an explanation to the low number of indigenous transconjugants found most of time when a plasmid-donor strain is introduced into soil.